Monitoring response to therapy by testing circulating tumor DNA in urine - Normanno, Nicola (Translational Cancer Research, 2017)
Husain and co-workers assessed the levels of epidermal growth factor receptor (EGFR) mutations in urine samples of advanced non-small cell lung cancer (NSCLC) patients receiving the third generation EGFR tyrosine kinase inhibitor (TKI) osimertinib (1).